Optimasi Sistem Antrian Pelayanan Teller di BRI Unit Sumbul Kabupaten Dairi - Sihombing, Nelly Naomi; Marpaung, Faridawaty (Jurnal Sains Indonesia, 2018)
This study aims to optimize the teller service queue system in a unit of Bank Rakyat Indonesia. By queuing theory, the queuing characteristic will be used as a calculated ratio. The observation results show that the queuing model that applied in the bank was (P/E_n/2) :(FCFS/8/8). To optimize the queue system it is necessary to change the model to (P/E_n/3) :(FCFS/8/8). Based on the calculation of waiting costs and facility costs, the optimal average service level is 31 customers/hour. So the addition of 1 teller facility would maximize the teller service and reduce 4,134 minutes of customer waiting time. [OPTIMIZATION OF THE TELLER SERVICE QUEUE SYSTEM AT BRI SUMBUL UNIT IN DISTRICT DAIRI](J. Sains Indon., 42(2): 38-43, 2018)Keywords:Queue System, Teller Service, Bank Rakyat Indonesia